2021
DOI: 10.3390/pharmaceutics13070993
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Dapagliflozin Containing Self-Nanoemulsifying Tablets: Formulation Design and In Vitro Characterization

Abstract: The 3D printing techniques have been explored extensively in recent years for pharmaceutical manufacturing and drug delivery applications. The current investigation aims to explore 3D printing for the design and development of a nanomedicine-based oral solid dosage form of a poorly water-soluble drug. A self-nanoemulsifying tablet formulation of dapagliflozin propanediol monohydrate was developed utilizing the semisolid pressure-assisted microsyringe (PAM) extrusion-based 3D printing technique. The developed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…Furthermore, several other studies reported the use of SSE printing techniques to fabricate tablets [ 51 , 68 , 69 , 70 , 71 ], oral films [ 72 ], and scaffolds [ 73 ], illustrating that SSE is an excellent technique to fabricate thermosensitive drugs at a lower temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several other studies reported the use of SSE printing techniques to fabricate tablets [ 51 , 68 , 69 , 70 , 71 ], oral films [ 72 ], and scaffolds [ 73 ], illustrating that SSE is an excellent technique to fabricate thermosensitive drugs at a lower temperature.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that coaxial SSE 3DP, where the coaxial extruder fixed to the printhead of the Ultimaker3 printer was connected through tubes to the syringe pump system, was used for the fabrication of propranolol-loaded drug delivery system [67]. Furthermore, several other studies reported the use of SSE printing techniques to fabricate tablets [51,[68][69][70][71], oral films [72], and scaffolds [73], illustrating that SSE is an excellent technique to fabricate thermosensitive drugs at a lower temperature.…”
Section: Semi-solid Extrusionmentioning
confidence: 99%
“…The objects were printed using an FDM 3D printer (Ultimaker S3, Utrecht, The Netherlands) at a temperature of 150 °C at a print speed of 50 mm/s. The bed temperature was kept at 80 °C and a 0.4 mm BB4 print head was used for the process [ 22 , 23 , 24 ]. The printing temperature was selected based on the preliminary thermal analysis, to ensure that the contents of our product to be filled in are not degraded by the heat of the nozzle.…”
Section: Methodsmentioning
confidence: 99%
“…More studies need to be conducted to explore the incorporation of SNEDDSs into 3D-printed tablets [ 22 , 23 , 24 ]. In the current study, we report the incorporation of the pre-formulated SNEDDSs into 3D-printed-container systems, for the delivery of two different drugs with inherent poor solubility, namely, curcumin (CUR) and lansoprazole (LNS).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, 3D printing has been studied systematically for the optimisation of 3D printed tablets [ 9 ] using a variety of technologies and materials (e.g., polymers, resins, hydrogels). The selection of the technology is usually related to the drug product specifications and such as water solubility, thermal stability, active dose and drug-excipient miscibility [ 10 , 11 ]. Selective laser sintering (SLS) was used by Awad et al to develop fast dissolving tablets of paracetamol for visually impaired patients.…”
Section: Introductionmentioning
confidence: 99%